Characteristics and prognosis of hepatocellular carcinoma in multi-transfused patients with thalassemia major. Experience of a single tertiary center. - Nikolaos Papadopoulos; Dimitrios Kountouras; Katerina Malagari; Maria Tampaki; Maria Theochari; John Koskinas (Mediterranean Journal of Hematology and Infectious Diseases)
Background: In this retrospective study, records of patients with thalassemia major (TM) diagnosed with hepatocellular carcinoma (HCC) from 2008‐2018 were reviewed in order to determine the survival rate and evaluate possible etiological factors associated with survival.